COVID-19 mRNA booster vaccine induces transient CD8+ T effector cell responses while conserving the memory pool for subsequent reactivation - Reinscheid, Matthias; Luxenburger, Hendrik; Karl, Vivien; Graeser, Anne; Giese, Sebastian; Ciminski, Kevin; Reeg, David B.; Oberhardt, Valerie; Röhlen, Natascha; Lang-Meli, Julia; Heim, Kathrin; Gross, Nina; et al. (Nature Communications, 2022)
Immunization with two mRNA vaccine doses elicits robust spike-specific CD8+ T cell responses, but reports of waning immunity after COVID-19 vaccination prompt the introduction of booster vaccination campaigns. However, the effect of mRNA booster vaccination on the spike-specific CD8+ T cell response remains unclear. Here we show that spike-specific CD8+ T cells are activated and expanded in all analyzed individuals receiving the 3rd and 4th mRNA vaccine shots. This CD8+ T cell boost response is followed by a contraction phase and lasts only for about 30-60 days. The spike-specific CD8+ T memory stem cell pool is not affected by the 3rd vaccination. Both 4th vaccination and breakthrough infections with Delta and Omicron rapidly reactivate CD8+ T memory cells. In contrast, neutralizing antibody responses display little boost effect towards Omicron. Thus, COVID-19 mRNA booster vaccination elicits a transient T effector cell response while long-term spike-specific CD8+ T cell immunity is conserved to mount robust memory recall targeting emerging variants of concern.